79 Effects of Age at First Breeding and Dietary Energy Level during the Rearing Period of Replacement Gilts. (10th April 2018) - Hosseindoust, A; Choi, Y; Oh, S; Kim, M; Kim, K Y; Hwang, S; Bu, M; Baidoo, S K; Chae, B J; Kim, J S
Abstract: A 3 × 2 factorial experiment was conducted to investigate the interactions between the mating age (early [EL], middle [MD] and late [LT]) of gilts at the first parity and dietary energy levels (High, 3320 kcal/kg; Low, 3120 kcal/kg). Eighty five gilts were selected with the average mating age of 222, 244 and 264 days for EL, MD and LT groups, respectively. The average weight of gilts were 141 ± 2, 153 ± 2 and 164 ± 2 for EL, MD and LT groups, respectively. The main effects of mating age, dietary energy, and their interaction were determined by the GLM procedure. There was no interaction between the mating age and dietary energy level. Mating age did not affect the growth rate, however, the high energy diets tended to increase the growth rate of gilts (P=0.083). Gilts in LT group had the highest (P<0.05) and gilts in EL group had the lowest (P<0.05) body weight (BW) at insemination. The backfat thickness (BFT) of gilts in LT group was higher than MD and EL groups (P<0.01). The BW of gilts at farrowing and weaning were greater (P<0.01) in LT than those of EL and MD. The BFT of gilts at farrowing was the lowest (P<0.01) in EL compared with MD and EL. There was a decrease (P<0.01) in BF loss during lactation in EL group, however, there was no further decrease (P>0.05) in BF loss in MD group compared with LT group. Gilts offered high energy diets did not show any changes (P>0.05) in BW and BFT. There was a decrease in feed intake (P<0.05) of gilts in LT, however, there was no change (P>0.05) in energy level groups. The insemination time and dietary energy levels had no effects (P>0.05) on weaning to service duration. There was no difference (P>0.05) in initial litter size among the groups, however, the number of weaned piglets was greater (P<0.05) in gilts in LT compared with EL. A greater final litter weight was observed for EL gilts (P<0.05). In conclusion, the age of gilts at the first mating influenced initial and final litter size of sows in the first parity, however, no influence of dietary energy level was found for performance traits including initial litter size and final litter weight.